The Influence of Green Perceived Value and Green Perceived Risk Perceptions on the Green Product Purchase Intention - Dhewi, T S; Adi Putra, I Wayan Jaman; ., Soeharto; Wahyudi, H D (KnE Social Sciences, 2018)
The purpose of this study is to acquire the influence of green perceived value and green perceived risk perceptions on the green products purchase intention. The study used three basic concepts of green marketing:the perception of green perceived value, the perception ofgreen perceived risk and interest in purchasing green products. The object of this study was the LCGC car (low cost green car) product which is considered as the economical and environmental friendly (green) car. LCGC car launching was one of the government’s effort to encourage automakers to make more environmentally friendly products. The survey of the research was conducted by using questionnaire to see the respondents’ views about green marketing. The empirical results showed that the perception of green values was positively correlated to theinterestin purchasing green products. Meanwhile, the perception of green perceived risk was negatively correlated to the interest inpurchasing green products.